PENGHULU AND MARRIAGE PROBLEMATICS OF BOUNDARY SOCIETY IN ENTIKONG AND SEKAYAM WEST KALIMANTAN - Muhammad ishom el-saha (AHKAM : Jurnal Ilmu Syariah, 2019)
This study focuses on the problem’s task of Penghulu about registering marriages and problems of unregistering marriages in the border areas of Indonesia and Malaysia, especially at Entikong-Sekayam, West Kalimantan. Communities in the area complained about the absence of KUA Staff which caused them not to receive maximum service. While on staff’s KUA perception, they have worked but the community does not want to adjust to them, such as obeying the applicable provisions. There is a possibility of a gap between written law as a reference for KUA Staff and customary law for communities. With the law in action approach, it’s found legal, social, economic, and political factors that cause marital problems in the border area.